Regulatory Role of the RNA N6-Methyladenosine Modification in Immunoregulatory Cells and Immune-Related Bone Homeostasis Associated With Rheumatoid Arthritis - Fan, Danping; Xia, Ya; Lu, Cheng; Ye, Qinbin; Xi, Xiaoyu; Wang, Qiong; Wang, Zheng; Wang, Chengyuan; Xiao, Cheng (Frontiers in Cell and Developmental Biology, 2021)
Rheumatoid arthritis (RA) is a systemic autoimmune disease for which the etiology has not been fully elucidated. Previous studies have shown that the development of RA has genetic and epigenetic components. As one of the most highly abundant RNA modifications, the N6-methyladenosine (m6A) modification is necessary for the biogenesis and functioning of RNA, and modification aberrancies are associated with various diseases. However, the specific functions of m6A in the cellular processes of RA remain unclear. Recent studies have revealed the relationship between m6A modification and immune cells associated with RA. Therefore, in this review, we focused on discussing the functions of m6A modification in the regulation of immune cells and immune-related bone homeostasis associated with RA. In addition, to gain a better understanding of the progress in this field of study and provide the proper direction and suggestions for further study, clinical application studies of m6A modification were also summarized.